Mental Burden of Hospital Workers During the COVID-19 Crisis: A Quanti-Qualitative Analysis - Luquiens, Amandine; Morales, Jennifer; Bonneville, Marion; Potier, Hugo; Perney, Pascal; Faure, Gilles; Canaguier, Astrid (Frontiers in Psychiatry, 2021)
Context: This study is a quanti-qualitative analysis of all contacts to a helpline service for hospital workers during the COVID-19 crisis. Our aim was to describe the nature of mental burden in hospital workers and factors subjectively associated to this burden from the workers' perspective. Methods: We included all 50 contacts from 25 different workers and 10 different professions over the course of 1 month. We described the corpus and reported the computerized qualitative analysis of summary of contacts. We performed a descendant hierarchical analysis and analyzed specificities of classes of age with a correspondence factor analysis. Results: The corpus was composed of three classes: (1) distress specific to the COVID-19 situation, (2) help provided, and (3) pre-existing psychological vulnerability. Factors subjectively responsible for mental distress were: (a) the contamination risk, (b) confinement, and (c) the rapidly evolving situation and changing instructions. Lack of “COVID-free time” seemed to increase negative emotions. Reassignment to a high viral density unit was a stressor, especially in older workers. Young workers mentioned pre-existing vulnerability more than others. Fear of death was shared by all classes of age, regardless of the objective risk of contamination. Discussion: Hospital workers experience mental distress factors both in common with the general population and specific to the hospital environment. Preserving and organizing support for the mental health of all hospital workers is a critical challenge, including those with poorly recognized professions. Leads for institutions to avoid additional stressors for hospital workers are presented. Young workers with pre-existing vulnerability seem particularly impacted.